2014
DOI: 10.1002/adma.201401603
|View full text |Cite
|
Sign up to set email alerts
|

Blue SHG Enhancement by Silver Nanocubes Photochemically Prepared on a RbTiOPO4 Ferroelectric Crystal

Abstract: Silver nanocubes with low size dispersion have been selectively photo-deposited on the positive surface of a periodically poled RbTiOPO4 ferroelectric crystal. The obtained nanocubes show preferential orientations with respect to the substrate suggesting epitaxial growth. The plasmonic resonances supported by the nanocubes are exploited to enhance blue SHG at the domain walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Figure 1(a) shows a scanning electron microscopy (SEM) image of the resultant nanocubes, which are characterized by an average edge length of around 60 nm and a low size dispersion (around 10%). As previously discussed [14], the well-defined cubic shape and the presence of preferential orientations of the nanocubes suggest the possibility of epitaxial growth related to the crystal structure of the RTP polar surface. Finally, for photodeposition times of 8 min and longer, large aggregates of Ag nanoparticles connected in a network-like arrangement with total size of several microns were obtained (hereafter type B structures).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Figure 1(a) shows a scanning electron microscopy (SEM) image of the resultant nanocubes, which are characterized by an average edge length of around 60 nm and a low size dispersion (around 10%). As previously discussed [14], the well-defined cubic shape and the presence of preferential orientations of the nanocubes suggest the possibility of epitaxial growth related to the crystal structure of the RTP polar surface. Finally, for photodeposition times of 8 min and longer, large aggregates of Ag nanoparticles connected in a network-like arrangement with total size of several microns were obtained (hereafter type B structures).…”
Section: Resultsmentioning
confidence: 71%
“…The effect of the different Ag nanostructures on the SHG intensity can be evaluated by comparing the obtained SHG signal before and after the deposition of the Ag structures. Three cases are analyzed: bare RTP, hybrid metal-RTP system with type A silver structures and hybrid metal-RTP system with type B complex aggregates (the effect of the silver nanocubes on the SHG has been the aim of a previous work [14]). The spatial maps of the SHG intensity obtained from the RTP surface are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 With this internal field, ferroelectric thin films are able to internally separate photo-generated carriers via the bulk photovoltaic effect, which has been used to achieve photochemical oxidation or reduction reaction, including surface decoration of metallic nanoparticles, decolorization of dye molecule, and water splitting. [2][3][4][5] Our recent studies revealed that the ferroelectric Pb(Zr,Ti)O 3 (PZT) films deposited on indium tin oxide (ITO) coated quartz substrate can work as a stable photocathode for water splitting. 6 However, the saturated photocurrent was limited to 110 lA cm À2 , mainly due to its large band-gap $3.5 eV.…”
mentioning
confidence: 99%
“…Other relatively simple methods consist on precipitating Ag‐nanoparticles in the frontiers of a periodically poled ferroelectric pattern under uniform UV light illumination or taking advantage of the pyroelectric effect . In this way, relevant enhancements in the SHG response have been obtained which are associated to the LSPR of the structures …”
Section: Introductionmentioning
confidence: 99%